SEED GERMINATION OF Avicennia marina (Forsk.) Vierh. BY PERICARP REMOVAL TREATMENT - Hery Purnobasuki; Edy Setiti Wida Utami (SEAMEO BIOTROP, 2016)
Avicennia marina is one species used for building coastal ecosystem stabilization on the Surabaya shores because of its tolerance to high salinity levels and resistance to wave energy. Its existence is threatened by various factors, including land conversion, pollution, and the construction of inter-island bridges. The growth of A. marina is currently limited by seed dormancy. To increase propagation efficiency, seed viability and vigor were compared based on collection dates and pericarp removal methods. The results showed no relationship between the salinity levels of soaking water or seed buoyancy and seed viability or vigor. Collection dates may influence seed viability and vigor, as seeds collected in October and November germinated more quickly than those collected in December, although there were no differences in total germination. Hand-peeled seeds germinated more slowly than soaked seeds for all collection dates, but with no differences in total germination. Seeds collected in October and November grew more vigorously than those collected in December.